Interaction of Insulin Resistance and Related Genetic Variants With Triglyceride-Associated Genetic Variants. (April 2016) - Klimentidis, Yann C.; Arora, Amit
Abstract : Background—: Several studies suggest that some triglyceride-associated single-nucleotide polymorphisms (SNPs) have pleiotropic and opposite effects on glycemic traits. This potentially implicates them in pathways such as de novo lipogenesis, which is presumably upregulated in the context of insulin resistance. We therefore tested whether the association of triglyceride-associated SNPs with triglyceride levels differs according to one's level of insulin resistance. Methods and Results—: In 3 cohort studies (combined n=12 487), we tested the interaction of established triglyceride-associated SNPs (individually and collectively) with several traits related to insulin resistance, on triglyceride levels. We also tested the interaction of triglyceride SNPs with fasting insulin–associated SNPs, individually and collectively, on triglyceride levels. We find significant interactions of a weighted genetic risk score for triglycerides with insulin resistance on triglyceride levels ( P interaction =2.73×10 −11 and P interaction =2.48×10 –11 for fasting insulin and homeostasis model assessment of insulin resistance, respectively). The association of the triglyceride genetic risk score with triglyceride levels is >60% stronger among those in the highest tertile of homeostasis model assessment of insulin resistance compared with those in the lowest tertile. Individual SNPs contributing to this trend include those in/near GCKR, CILP2, and IRS1, whereas PIGV-NROB2 and LRPAP1 display an opposite trend of interaction. In the pooled data set, we also identify a SNP–by–SNP interaction involving a triglyceride-associated SNP, rs4722551 near MIR148A, with a fasting insulin–associated SNP, rs4865796 in ARL15 ( P interaction =4.1×10 −5 ). Conclusions—: Our findings may thus provide genetic evidence for the upregulation of triglyceride levels in insulin-resistant individuals, in addition to identifying specific genetic loci and a SNP–by–SNP interaction implicated in this process. Abstract : Supplemental Digital Content is available in the text.